1986
DOI: 10.1530/acta.0.112s147
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment of constitutional delay in growth and development: effect of dose on predicted versus definitive height

Abstract: The outcome of treatment in 3 groups of boys with constitutional delay in growth and development given monthly intramuscular injections of testosterone enanthate 200 mg (22 subjects) 100 mg (10 subjects) and 50 mg (12 subjects) was compared with the outcome in a control group (14 subjects) without treatment. The 4 groups were similar in chronological age, height, height age, bone age, height age/bone age ratio, pubertal development and had similar predicted adult heights. All treated subjects achieved an excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 3 publications
(5 reference statements)
3
21
0
Order By: Relevance
“…Generally. CDGP is regarded as a nor mal variant of growth in childhood with a good final prognosis [4,[13][14][15][16], In our study we could show that bone age and growth were retarded to the same degree as it had been observed previously [7], When this delay in skeletal maturation finally ends the patients are then able to reach their genetic target height.…”
Section: Discussionsupporting
confidence: 66%
“…Generally. CDGP is regarded as a nor mal variant of growth in childhood with a good final prognosis [4,[13][14][15][16], In our study we could show that bone age and growth were retarded to the same degree as it had been observed previously [7], When this delay in skeletal maturation finally ends the patients are then able to reach their genetic target height.…”
Section: Discussionsupporting
confidence: 66%
“…Doses ranging from 50 to 200 mg IM monthly have positive effects on growth velocity without unduly advancing the bone age, with no detrimental effect on adult height, except at the high doses [86]. Interestingly studies have shown that 6 months of testosterone treatment does not affect the tempo of puberty [87].…”
Section: Testosteronementioning
confidence: 99%
“…This suggests that the genetic factors account for a reduced adult stature in many of those patients. In 3 studies, the administration of long-acting esters of testosterone using dosages of 200 mg/month or more was shown to result in some pos sible reduction (mean: 2-5 cm) of adult height when compared to untreated patients [22,23,25], In contrast, lower dosages of testosterone given for up to 1 year did not affect final height which was slightly above that of untreated patients [23. 24].…”
Section: Influence O F Age At Onset O F Puberty On Final Heightmentioning
confidence: 99%